L'enquête publique et les critères de contrôle judiciaire des fonctions exercées par les enquêteurs - Crête, Raymonde (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
The public inquiry has long been used to gather information of concern to the State in order that the best decisions may be made according to the information thereby obtained. The Quebec legislator has, therefore, foreseen the need for different laws or particular provisions that would enable the government to make use of this procedure. Among these we find the laws governing commissions of inquiry, police, municipal commissions, coroners and arson investigations. The public often follows closely the proceedings of such inquiries, which, consequently, become a means of informing, educating, and establishing a dialogue with, the public. However, certain public inquiries, such as the Quebec Commission of Inquiry on Organized Crime, the commission of inquiry on freedom of unionization and the Keable Commission, run the risk of affecting the rights of citizens, namely those summoned to appear during such hearings as well as those whose names appear in the testimony given. Hence, some individuals may see their reputations tarnished because of facts brought to light during the inquiry, lose their jobs as a result of commission recommendations or many later have to face either civil or criminal prosecution. It is, therefore, important that such persons be given access to the courts, in order to either challenge the jurisdiction of the commission or demand that the inquiry respect the rules of natural justice.In this area, judicial review depends on the characterization of the method of operation of the public inquiry as a whole, i.e. as the exercise by the commissioners of a recommendatory power, or of interlocutory decisions taken during the course of the inquiry. Depending on the judicial or administrative nature of the activity concerned, the courts will decide whether or not to exercise their superintending and reforming powers. Thus, the courts will intervene only if the function exercised is of a judicial nature. In this regard, the courts deem that an administrative body exercises a judicial function, on the one hand when it determines the rights of individuals and, on the other, when such a body has a duty to act judicially. Apart from some rare exceptions, the courts have ruled that the exercise of the power of inquiry generally does not trench on the rights of citizens and that such a power is therefore administrative in nature. At present, the issue as to whether the inquiry determines the rights of individuals is considered by the courts in the light of either one of two theories, which can be labelled the binary and global theories. Supporters of the binary theory feel that the inquiry and the decisions which may proceed therefrom represent two quite distinct stages and the interference with the rights of individuals can only occur when a decision is made. We find an illustration of this reasoning in, among others cases, Guay v. Lafleur and St-John v. Fraser. Proponents of the second theory are agreed that the decision is an integral part of the inquiry process and that interference with rights occurs at the inquiry level itself. This argument is exemplified adequately by the judgement in Saulnier v. Quebec Police Commission. This paper also examines the characterization of interlocutory decisions made by a commission in the course of its proceedings. In this respect, the courts feel that coercive powers are of a judicial nature, while decisions concerning the administration of evidence are seen as administrative. A study of the abundant jurisprudence in this area leads us to conclude that the Quebec legislator should provide for a specific recourse, similar to that existing presently in Ontario, which would allow citizens access to the courts to challenge decisions made by commissions of inquiry.